2012
DOI: 10.1371/journal.pone.0035960
|View full text |Cite
|
Sign up to set email alerts
|

Clara Cell 10-kDa Protein Gene Transfection Inhibits NF-κB Activity in Airway Epithelial Cells

Abstract: BackgroundClara cell 10-kDa protein (CC10) is a multifunctional protein with anti-inflammatory and immunomodulatory effects. Induction of CC10 expression by gene transfection may possess potential therapeutic effect. Nuclear factor κB (NF-κB) plays a key role in the inflammatory processes of airway diseases.Method/ResultsTo investigate potential therapeutic effect of CC10 gene transfection in controlling airway inflammation and the underlying intracellular mechanisms, in this study, we constructed CC10 plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Secondly, even after adjustment in multivariable models for age, sex, baseline BMI, pack years of smoking and baseline current smoking status, the observed effect not only persists but is strengthened. These observed associations are consistent with published results wherein CC16 has been associated with anti-inflammatory activity in lungs [2,13] and with regression of bronchial dysplasia in former smokers [14]. Taken together, these studies support an integral role for this protein in lung health.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Secondly, even after adjustment in multivariable models for age, sex, baseline BMI, pack years of smoking and baseline current smoking status, the observed effect not only persists but is strengthened. These observed associations are consistent with published results wherein CC16 has been associated with anti-inflammatory activity in lungs [2,13] and with regression of bronchial dysplasia in former smokers [14]. Taken together, these studies support an integral role for this protein in lung health.…”
supporting
confidence: 92%
“…
Club cell protein (CC16 in humans) plays a crucial role in maintaining homeostasis of the airway epithelium [1] and has anti-inflammatory activity in the lung [2]. Serum CC16 levels are low in cigarette smokers [3] and increase following smoking cessation [4], but patients with chronic obstructive pulmonary disease (COPD) show progressive decrease in CC16 with disease severity [5].
…”
mentioning
confidence: 99%
“…CC16 −/− nasal epithelial cells produce greater amounts of IL-8 when activated with IL-1β than cells from WT mice both in vitro and in vivo 113 . Moreover, plasmid-mediated over-expression of CC16 in the nasal epithelium of CC16 −/− mice reduces their increased release of IL-8 when IL-1β is administered 113 .…”
Section: Club Cell Protein-16 (Cc16)mentioning
confidence: 91%
“…CC16 −/− nasal epithelial cells produce greater amounts of IL-8 when activated with IL-1β than cells from WT mice both in vitro and in vivo 113 . Moreover, plasmid-mediated over-expression of CC16 in the nasal epithelium of CC16 −/− mice reduces their increased release of IL-8 when IL-1β is administered 113 . Gamez et al reported that epithelial cells isolated from COPD airways produce more IL-8 compared with cells isolated from healthy smoker and non-smoker airways, and this increased release of IL-8 was reduced by adding rCC16 to the COPD cell cultures 114 .…”
Section: Club Cell Protein-16 (Cc16)mentioning
confidence: 91%
See 1 more Smart Citation